Putting Research Evidence to Work: Key Issues for Research Utilisation in Irish Children's Services - BUCKLEY, HELEN (Children Acts Advisory Board, 2009)
Following its establishment in July 2007 the Board of the CAAB identified as a key strategic objective the need to strengthen the knowledge base of children?s services. In order to fully meet this objective the Board believes that it is necessary to develop a research capacity that effectively utilises the internal resources of the children?s sector and creates strong links with academic and research organisations nationally and internationally. The Board is very aware of the cost of research, and in particular the cost of the lost opportunity when research is not applied. In developing our research programme the Board believed that it was critical to establish an understanding of the elements necessary to ensure that the research being carried out was the most appropriate and that its findings could be understood and applied across the sector. Our first commission was therefore this study ? Putting Research Evidence to Work: Key Issues for Research Utilisation in Irish Children?s Services.
PUBLISHED
Keywords: Administrative Staff Authors